The Effect of Necitumumab in Combination with Gemcitabine plus Cisplatin on Tolerability and on Quality of Life: Results from the Phase 3 SQUIRE Trial. Issue 6 (June 2016) - Reck, Martin; Socinski, Mark A.; Luft, Alexander; Szczęsna, Aleksandra; Dediu, Mircea; Ramlau, Rodryg; Losonczy, György; Molinier, Olivier; Schumann, Christian; Gralla, Richard J.; Bonomi, Philip; Brown, Jacqueline; et al.
ABSTRACT : Introduction: : Necitumumab, a second‐generation, recombinant human immunoglobulin G1 epidermal growth factor receptor antibody in the phase 3 SQUIRE trial (NCT00981058), increased survival benefit for patients randomized to receive necitumumab plus gemcitabine‐cisplatin compared with those who received gemcitabine‐cisplatin. Here we characterize health‐related quality of life (HRQoL) and tolerability results. Methods: : A total of 1093 patients with stage IV squamous non–small cell lung cancer were randomized 1:1 to receive necitumumab (800 mg absolute dose intravenously [IV]) plus gemcitabine‐cisplatin (gemcitabine = 1250 mg/m 2 IV on days 1 and 8; cisplatin = 75 mg/m 2 IV on day 1) or gemcitabine‐cisplatin alone (every 21 days) for up to six cycles. Patients receiving necitumumab plus gemcitabine‐cisplatin without disease progression continued necitumumab until progression. HRQoL was measured by Eastern Cooperative Oncology Group performance status, the Lung Cancer Symptom Scale (LCSS), and the European Quality of Life Five‐Dimensions questionnaire. Efficacy and LCSS outcomes were analyzed using the baseline maximum severity score of the LCSS. Tolerability was measured in terms of exposure to the study treatment and adverse events. Hospitalization rates were collected. Results: : Most patients in both study arms similarly maintained Eastern Cooperative Oncology Group performance status and comparable LCSS and European Quality of Life Five‐Dimensions questionnaire assessments. Patients with a higher baseline LCSS had a greater survival benefit on the necitumumab arm. Chemotherapy exposure was similar in both treatment arms; 51% of patients on the necitumumab plus gemcitabine‐cisplatin arm continued on single‐agent necitumumab. The most frequent grade 4 adverse events were neutropenia (6.1% versus 7.9%) and thrombocytopenia (3.2% versus 4.3%) in the necitumumab plus gemcitabine‐cisplatin versus gemcitabine‐cisplatin arms, respectively. Hospitalizations were slightly higher with necitumumab plus gemcitabine‐cisplatin (36.4%) than with gemcitabine‐cisplatin (34.0%). Conclusions: : The addition of necitumumab to gemcitabine‐cisplatin was well tolerated, did not negatively affect HRQoL or toxicity, and particularly benefited patients with more severe baseline symptoms or lower HRQoL.